Patients’ preimplantation genetic testing decision-making experience: an opinion on related psychological frameworks - Pastore, L M (Hum Reprod Open, 2019)
The process of deciding whether to pursue preimplantation genetic testing (PGT) of an embryo is highly stressful for individuals and couples and has adverse emotional consequences (e.g. distress and uncertainty). PGT influences patients’ lives in both positive and negative ways and is experienced at an individual level, as a dyadic unit, as a family member and as part of the society. Here, we argue that providing a conceptual framework with which to understand the `experience of decision making’ about PGT for monogenic disease (PGT-M) testing specifically, as well as the factors contributing to `decisional distress’ and `uncertainty’ that patients endure as a result—apart from what decision they make—is crucial to optimizing patient counseling, satisfaction and outcomes in the field of ART. Derived from psychological theory, the framework proposed here identifies three categories of contributing factors to decisional distress and uncertainty in considering PGT-M; namely, ‘intraindividual’, ‘interpersonal’ and ‘situational’ factors. We reviewed evidence from the PGT literature to inform our framework. Well-accepted theories of stress and health decision making were also reviewed for their relevance to PGT-M decision making, focusing on potential distress and uncertainty. Our novel conceptual framework can be used to inform clinical practice, to advance research and to aid the development of interventions for individuals and couples who are deciding whether or not to use PGT-M. Alleviating emotional distress and uncertainty can improve patients’ well-being during their reproductive journey.